2021
DOI: 10.3390/en14216890
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Using Capillary Active Interior Insulation in a Cold Climate

Abstract: The retrofitting of cultural heritage buildings for energy efficiency often requires the internal thermal insulation of external walls. Most of the in situ studies of capillary active interior insulation were performed in mild oceanic climate regions, and they showed an excellent performance. However, as a large part of Central–Eastern Europe belongs to a continental climate with cold winters and long periods of temperatures below the freezing temperature, the applicability of the capillary active interior ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…If the possibility of mould growth and interstitial condensation to occur behind the insulation system was found to be probable or high, individual case assessment in the design phase was found always necessary to guarantee the damage-free refurbishment [9]. A study on similar materials to be used in similar retrofit-projects was presented by Antolinc et.al., located in continental climate [10]. The results confirm that capillary-active insulation materials proved to be unsuitable for improving the thermal insulation of older buildings built with a similar external wall construction, i.e., single masonry walls and conclude that only a vapour-tight systems can be recommended.…”
Section: Introductionmentioning
confidence: 54%
“…If the possibility of mould growth and interstitial condensation to occur behind the insulation system was found to be probable or high, individual case assessment in the design phase was found always necessary to guarantee the damage-free refurbishment [9]. A study on similar materials to be used in similar retrofit-projects was presented by Antolinc et.al., located in continental climate [10]. The results confirm that capillary-active insulation materials proved to be unsuitable for improving the thermal insulation of older buildings built with a similar external wall construction, i.e., single masonry walls and conclude that only a vapour-tight systems can be recommended.…”
Section: Introductionmentioning
confidence: 54%
“…The glue mortar can capture a large amount of moisture [22]. In another study, [23] conclusions are that capillary-active interior insulation cannot be applied in a cold continental climate and vapor-tight insulation has to be applied. They found that condensation in the masonry can appear if the capillary-active interior insulation with a relatively small water vapor resistance factor, high indoor moisture load, and no adhesive glue is applied.…”
Section: Introductionmentioning
confidence: 99%
“…Hygrothermal behavior during winter conditions shows that if a capillary active system has risks of interstitial condensation due to high level of an accumulated moisture content in the wall and the glue mortar, a vapor-tight system is preferable [4]. Antolinc et al (2021) found that in a room with very high indoor relative humidity, the capillary active interior insulation is not a suitable solution for improving the thermal insulation of buildings in a cold continental climate and vapor-tight insulation needs to be applied [33]. However, moist indoor air can diffuse outwards into the masonry due to mechanical damage to the vapor barrier or poor craftsmanship [34].…”
Section: Introductionmentioning
confidence: 99%